2008
DOI: 10.1002/jrs.1901
|View full text |Cite
|
Sign up to set email alerts
|

The first Raman spectroscopic study of San rock art in the Ukhahlamba Drakensberg Park, South Africa

Abstract: San rock art sites are found throughout southern Africa; unfortunately this unique heritage is rapidly being lost through natural weathering processes, which have been the focus of various studies conducted in the uKhahlamba Drakensberg Park since 1992. It has recently been shown that the ability of Raman spectroscopy to identify salts on rock faces on a micro, as well as nano scale, can make a contribution to these projects.In order to test the feasibility of undertaking on-site analyses, a small rock fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 42 publications
7
82
0
1
Order By: Relevance
“…La composición mineral, los materiales de procedencia natural, los aglutinantes orgánicos y los procesos de manufactura de los colorantes constituyen el punto de interés prioritario de la caracterización de pigmentos. Entre todos estos componentes suelen ser los aglutinantes, preferentemente orgánicos, los más difíciles de detectar a causa de su gran diversidad y del comprensible proceso de degradación experimentado a lo largo de miles de años, por lo que, en caso de preservarse, se encuentran a niveles de simples trazas, lo que dificulta de manera considerable su apreciación (Cristini et al, 2010;Hernanz et al, 2007;Prisloo et al, 2008;Smith y Clark, 2004). El hecho de contar con una placa de cuarcita localizada en el mencionado abrigo del Friso del Terror, desprendida de forma natural de su panel original y que conservaba restos de pinturas rupestres -representación parcial de dos barras (Fig.…”
Section: © Universidad De Salamancaunclassified
“…La composición mineral, los materiales de procedencia natural, los aglutinantes orgánicos y los procesos de manufactura de los colorantes constituyen el punto de interés prioritario de la caracterización de pigmentos. Entre todos estos componentes suelen ser los aglutinantes, preferentemente orgánicos, los más difíciles de detectar a causa de su gran diversidad y del comprensible proceso de degradación experimentado a lo largo de miles de años, por lo que, en caso de preservarse, se encuentran a niveles de simples trazas, lo que dificulta de manera considerable su apreciación (Cristini et al, 2010;Hernanz et al, 2007;Prisloo et al, 2008;Smith y Clark, 2004). El hecho de contar con una placa de cuarcita localizada en el mencionado abrigo del Friso del Terror, desprendida de forma natural de su panel original y que conservaba restos de pinturas rupestres -representación parcial de dos barras (Fig.…”
Section: © Universidad De Salamancaunclassified
“…Considering that many works (e.g., Rudner, 1983;Prinsloo et al, 2008) cite organic attributes to the binders/extenders of San pigments (animal fats, egg, blood, urine, etc. ) and that the present data show that light can penetrate the sandstone, it seems notable that there are few reports (see Arocena, Hall, & Meiklejohn, 2008) of subsurface biological activity associated with the paintings.…”
Section: Thoughts and Questionsmentioning
confidence: 99%
“…A general lack of understanding of rock weathering mechanisms is considered to be the major reason for the inadequacy of previous research into rock art conservation and preservation in southern Africa (Meiklejohn, Hall, & Davis, 2009). The most recent research (see Hall, Meiklejohn, & Arocena, 2007a;Hall et al, 2007b, Arocena, Hall, & Meiklejohn, 2008, Prinsloo et al, 2008 has shifted the focus away from investigating weathering of the rock on which the art is located, to the interface between the rock and the pigments and that of pigment-to-pigment within the paintings themselves. Improved techniques from weathering research are able to measure conditions at the rock surface where the art is found (Hall, Meiklejohn, & Arocena, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent characterization studies have provided new insights on black paints, revealing that carbon-based paints were indeed used (Prinsloo et al 2008;Tournié et al 2011;Bonneau et al 2012;Hoerlé et al 2016). Following these studies, we successfully obtained three dates on black paintings from collapsed rock flakes at site RSA TYN2 (South Africa) using a modified ABA pretreatment protocol (Bonneau et al 2011).…”
Section: Introductionmentioning
confidence: 99%